2018
DOI: 10.3389/fpsyg.2018.02396
|View full text |Cite
|
Sign up to set email alerts
|

EmojiGrid: A 2D Pictorial Scale for the Assessment of Food Elicited Emotions

Abstract: Research on food experience is typically challenged by the way questions are worded. We therefore developed the EmojiGrid: a graphical (language-independent) intuitive self-report tool to measure food-related valence and arousal. In a first experiment participants rated the valence and the arousing quality of 60 food images, using either the EmojiGrid or two independent visual analog scales (VAS). The valence ratings obtained with both tools strongly agree. However, the arousal ratings only agree for pleasant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 132 publications
(211 reference statements)
3
92
0
Order By: Relevance
“…Schouteten, Verwaeren, Gellynck, et al () performed correspondence analysis on their emoji‐based CATA data and reported that over 90% of the variance was explained by the first dimension, which represented the emotional valence of the emojis; these findings support the results of the present research. Although some researchers argue that methods should include both emotional valence and arousal (i.e., Toet et al, ), the authors feel that when conducting research with children there may be a benefit to utilizing simple methods using only valence to ensure the children fully understand the intended emotion. The addition of emotional arousal does not add as much value as valence (Schouteten, Verwaeren, Gellynck, et al, ), and could make tasks become confusing or taxing for the participant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Schouteten, Verwaeren, Gellynck, et al () performed correspondence analysis on their emoji‐based CATA data and reported that over 90% of the variance was explained by the first dimension, which represented the emotional valence of the emojis; these findings support the results of the present research. Although some researchers argue that methods should include both emotional valence and arousal (i.e., Toet et al, ), the authors feel that when conducting research with children there may be a benefit to utilizing simple methods using only valence to ensure the children fully understand the intended emotion. The addition of emotional arousal does not add as much value as valence (Schouteten, Verwaeren, Gellynck, et al, ), and could make tasks become confusing or taxing for the participant.…”
Section: Discussionmentioning
confidence: 99%
“…First, the K‐State emoji scale was tested in two countries which do not represent emoji usage across the world. The scale has the potential to still be used or understood differently by other demographics, however, other research has shown that emojis do in fact have similar recognition and meanings in many countries and cultures globally (Jaeger, Vidal, et al, ; Kaneko et al, ; Toet et al, ). Second, participants evaluated the stimuli with two different scales in the same sitting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphical affective self-report tools are an attractive alternative to verbal instruments, since they enable users to report their feelings more intuitively through figural elements that represent their current affective state (for extensive discussions on the benefits of these tools see [19,20]). Instead of asking users to phrase their emotions, these tools use the human capability to intuitively and reliably relate graphical elements to human emotions [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%